K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

20 tháng 8 2018

a) b 3 + 3 b 2 + 2 b 3 + 1 .          b) 0.

3 tháng 9 2018

\(x^4-13x^3+13x^2-13x+2014\)

\(=x^4-\left(x+1\right)x^3+\left(x+1\right)x^2-\left(x+1\right)x+x+2002\)

\(-x^4-x^4-x^3+x^3+x^2-x^2-x+x+2002\)

\(=2002\)

3 tháng 9 2018

\(x^4-13x^3+13x^2-13x+2014\)

\(=x^4-\left(x+1\right)x^3+\left(x+1\right)x^2-\left(x+1\right)x+x+2002\)

\(=x^4-x^4-x^3+x^3+x^2-x^2-x+x+2002\)

\(=2002\)

31 tháng 7 2023

v) \(\left(-\dfrac{1}{2}x+3\right)\left(2x+6-4c^3\right)\)

\(=-\dfrac{1}{2}\left(2x+6-4c^3\right)+3\left(2x+6-4c^3\right)\)

\(=-x^2-3x+2c^3x+6x+18-12c^3\)

\(=-x^2+3x+2c^3x+18-12c^3\)

f) \(\left(2x-5\right)\left(x^2-x+3\right)\)

\(=2x\left(x^2-x+3\right)-5\left(x^2-x+3\right)\)

\(=2x^3-2x^2+6x-5x^2+5x-15\)

\(=2x^3-7x^2+11x-15\)

w) \(\left(3x+1\right)\left(x^2-2x-5\right)\)

\(=3x\left(x^2-2x-5\right)+\left(x^2-2x-5\right)\)

\(=3x^3-6x^2-15x+x^2-2x-5\)

\(=3x^3-5x^2-17x-5\)

x) \(\left(6x-3\right)\left(x^2+x-1\right)\)

\(=6x\left(x^2+x-1\right)-3\left(x^2+x-1\right)\)

\(=6x^3+6x^2-6x-3x^2-3x+3\)

\(=6x^3+3x^2-9x+3\)

y) \(\left(5x-2\right)\left(3x+1-x^2\right)\)

\(=5x\left(3x+1-x^2\right)-2\left(3x+1-x^2\right)\)

\(=15x^2+5x-5x^3-6x-2+2x^2\)

\(=-5x^3+17x^2-x-2\)

z) \(\left(\dfrac{3}{4}x+1\right)\left(4x^2+4x+4\right)\)

\(=\dfrac{3}{4}x\left(4x^2+4x+4\right)+\left(4x^2+4x+4\right)\)

\(=3x^3+3x^2+3x+4x^2+4x+4\)

\(=3x^3+7x^2+7x+4\)

f: =2x^3-2x^2+6x-5x^2+5x-15

=2x^3-7x^2+11x-15

w: =3x^3-6x^2-15x+x^2-2x-5

=3x^3-5x^2-17x-5

x: =6x^3+6x^2-6x-3x^2-3x+3

=6x^3+3x^2-9x+3

y: =(5x-2)(-x^2+3x+1)

=-5x^3+15x^2+5x+2x^2-6x-2

=-5x^3+17x^2-x-2

z: =3x^3+3x^2+3x+4x^2+4x+4

=3x^3+7x^2+7x+4

15 tháng 9 2019

\(a,x^4-7x^2+6\)

\(=x^4-x^2-6x^2+6\)

\(=x^2\left(x^2-1\right)-6\left(x^2-1\right)\)

\(=\left(x^2-6\right)\left(x^2-1\right)\)

\(=\left(x+\sqrt{6}\right)\left(x-\sqrt{6}\right)\left(x+1\right)\left(x-1\right)\)

15 tháng 9 2019

\(b,x^4+2x^2-3=x^4+3x^2-x^2-3\)

\(=x^2\left(x^2+3\right)-\left(x^2+3\right)\)

\(=\left(x^2-1\right)\left(x^2+3\right)\)

\(=\left(x+1\right)\left(x-1\right)\left(x^2+3\right)\)